(untitled) (Marketing Journal, 2025)
The article presents an empirical assessment of management mechanisms for technological modernization processes in industrial enterprises across regions. Core indicators such as the technological index, equipment depreciation, energy intensity, and the sha re of skilled labor were used for evaluation. Regional disparities in technological development levels were identified, and measures for their reduction were proposed. Cluster analysis, correlation, and regression methods were applied to substantiate the i mpact of technological investments on production efficiency. The 584 conclusions are supported by practical recommendations related to governance, financing, infrastructure, and workforce development.